2017
DOI: 10.1007/s12195-017-0498-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprotection Across the Tumor Border: Cancer Cell Response to Doxorubicin Depends on Stromal Fibroblast Ratios and Interstitial Therapeutic Transport

Abstract: Introduction-Increasing evidence suggests that the tumor microenvironment reduces therapeutic delivery and may lead to chemotherapeutic resistance. At tumor borders, drug is convectively transported across a unique microenvironment composed of inverse gradients of stromal and tumor cells. These regions are particularly important to overall survival, as they are often missed through surgical intervention and contain many invading cells, often responsible for metastatic spread. An understanding of how cells in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…The in vivo tumor microenvironment is inherently spatially heterogeneous, and researchers are starting to examine how this cellular and extracellular heterogeneity may influence treatment response. Logsdon et al, found that MDA-MB-231 cells in mixed, 3D culture with fibroblasts were more resistant to 10 µM doxorubicin at low ratios of tumor to stromal cells (4:1) but equally affected by the drug at higher ratios (1:4) [39]. Shen at al., found similar results using a micro-patterned interface of tumor to stromal cells wherein MCF-7 cell proliferation was inhibited by reversine at the interface but not in the bulk [46].…”
Section: Assessing Drug Response In Multi-cellular Culture Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The in vivo tumor microenvironment is inherently spatially heterogeneous, and researchers are starting to examine how this cellular and extracellular heterogeneity may influence treatment response. Logsdon et al, found that MDA-MB-231 cells in mixed, 3D culture with fibroblasts were more resistant to 10 µM doxorubicin at low ratios of tumor to stromal cells (4:1) but equally affected by the drug at higher ratios (1:4) [39]. Shen at al., found similar results using a micro-patterned interface of tumor to stromal cells wherein MCF-7 cell proliferation was inhibited by reversine at the interface but not in the bulk [46].…”
Section: Assessing Drug Response In Multi-cellular Culture Systemsmentioning
confidence: 99%
“…The presence of stromal cells (cancer-associated fibroblasts, pericytes, or adipocytes) has been shown to drastically alter drug response, ranging from promoting drug resistance to increasing drug sensitivity [39][40][41][42][43][44]. Using multicellular cultures can account for tissue level interactions and therefore may be more physiologically relevant than monocultures.…”
Section: Assessing Drug Response In Multi-cellular Culture Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation in synergistic treatment was also made in a similar model with MDA‐MB‐231 and stromal HTB‐125 cells, where without Tranilast, DOX therapy lead to increased fibrosis and thus drug resistance (Saini et al, 2018). In a similar investigation of CAF influence, the ratio of MDA‐MB‐231:human dermal fibroblast was tested for possible effects on DOX efficacy while incorporating delivery via interstitial flow (Logsdon, Beeghly, & Munson, 2017). The fibroblasts were more chemoprotective at low density (4:1) than at 1:1 or 1:4 (Logsdon et al, 2017).…”
Section: Hydrogel‐based Modelsmentioning
confidence: 99%
“…In a similar investigation of CAF influence, the ratio of MDA‐MB‐231:human dermal fibroblast was tested for possible effects on DOX efficacy while incorporating delivery via interstitial flow (Logsdon, Beeghly, & Munson, 2017). The fibroblasts were more chemoprotective at low density (4:1) than at 1:1 or 1:4 (Logsdon et al, 2017).…”
Section: Hydrogel‐based Modelsmentioning
confidence: 99%